Relationship between the frequency of falls, fear of falling and functional abilities in women aged 65 and over - Ivanović Sunčica; Trgovčević Sanja; Kocić Biljana; Tomašević-Todorović Snežana Β.; Jeremić-Knežević Milica Β.; Knežević Aleksandar (Vojnosanitetski Pregled)
Background/Aim. An increased tendency to fall and subsequent occurrence of injuries due to decline in the functional abilities are some of the many problems in older persons. The aim of the study was t o determine the differences in functional abilities and the expressiveness of fear of falling be-tween the women aged 65 and over who experienced a fall in the past 12 months (G1) and those that did not (G2). Methods. In this cross-sectional study, 236 women aged 65 and over were included. Fall history was based on self–reporting, the fear of a fall was estimated based on The Falls Efficacy Scale International – FESI, while the functional ability was measured by The Lawton Instrumental Activities of Daily Living – IADL. Results. Just under half of the women in the sample reported that one or more falls occurred in the last 12 months. Through the connectivity analysis, in both groups (G1 and G2), coefficients of correlation achieved statistical significance between the functional ability and fear of falling. A strong and negative correlation between IADL and FESI score in both groups, G1 (ρ = -0.695; p < 0.001) and G2 (ρ = -0.657; p < 0.001), was confirmed. Conclusion. The improvement of functional ability in women aged 65 and over could lower the risk of falling in this population.